Non-covalent cyclic peptides simultaneously targeting Mpro and NRP1 are highly effective against Omicron BA.2.75 - Yin, Shengnan; Mei, Shuang; Li, Zhiqin; Xu, Zhen; Wu, Yuting; Chen, Xiujuan; Liu, Dongmei; Niu, Miao-Miao; Li, Jindong (Frontiers in Pharmacology, 2022)
The absence of effective vaccines against the latest epidemic variant Omicron has resulted in an upsurge in infections and deaths. The main protease (Mpro) of SARS-CoV-2 and human neuropilin-1 (NRP1), two less mutable proteins, have been reported to be crucial for SARS-CoV-2 replication and entry into host cells, respectively. Their dual blockade may avoid vaccine failure caused by continuous mutations of the SARS-CoV-2 genome and exert synergistic antiviral efficacy. Herein, four cyclic peptides non-covalently targeting both Mpro and NRP1 were identified using virtual screening. Among them, MN-2 showed highly potent affinity to Mpro (Kd = 18.2 ± 1.9 nM) and NRP1 (Kd = 12.3 ± 1.2 nM), which was about 3,478-fold and 74-fold stronger than that of the positive inhibitors Peptide-21 and EG3287. Furthermore, MN-2 exhibited excellent anti-infective activity against the pseudotyped variant Omicron BA.2.75 without obvious toxicity to normal host cells. These data demonstrated that MN-2, a novel non-covalent cyclic peptide, is a promising agent against Omicron BA.2.75.